Long term efficacy and safety of Lorlatinib in ALK-positive non-small cell lung cancer: A case report - Jialin Qian; Tianqing Chu (Current Problems in Cancer: Case Reports)
Background: Anaplastic lymphoma kinase (ALK) rearrangement is a key oncogenic driver promoting the expression of ALK protein in non-small cell lung cancer (NSCLC). ALK tyrosine kinase inhibitors (TKIs) have significantly improved survival benefits. Exploring the optimal therapeutic regimens for ALK+ NSCLC patients is of crucial clinical significance. Case description: A 67-year-old woman with no history of smoking was diagnosed with locally advanced ALK+ lung adenocarcinoma (stage IIIC) at the first diagnosis. The patient was enrolled in the CROWN study and was randomized to receive lorlatinib treatment, and the re-examination 1 month later showed that the lung lesions were significantly reduced. The efficacy was PR, and the PFS had reached 72 months at the last follow-up. During the treatment, the patient tolerated well, no serious adverse events occurred, and the tumor was effectively controlled. Conclusions: Lorlatinib is an effective 1 L treatment option for patient with advanced ALK-positive NSCLC, which can bring long-term benefits to patients.